2005
DOI: 10.1677/joe.1.06063
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of experimental autoimmune encephalomyelitis using estrogen receptor-selective ligands

Abstract: Estrogens have been shown to modulate disease activity in experimental autoimmune encephalomyelitis (EAE), the mouse model for multiple sclerosis. Consistent with these findings, the severity of disease is reduced in pregnant women with multiple sclerosis when levels of estrogens are high. Estrogens bind to two known estrogen receptors (ER), ER and ER . The relative contribution of these receptors to estrogen-mediated suppression of EAE was explored using ER-selective ligands. The ER antagonist ICI 182 780 rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 52 publications
6
69
1
3
Order By: Relevance
“…Morales et al [170] demonstrated that treatment with an ERa ligand is sufficient to recapitulate the estrogen-mediated protection in EAE, consistent with a report by Elloso et al [69] that demonstrated that treatment with an ERa, but not an ERb, ligand could reduce acute EAE disease severity. The degree of preservation of neuronal integrity in the gray matter of estradiol and ERa ligand-treated mice with EAE in this study was striking, and this has major implications for neurodegenerative changes that occur ''beyond the lesion" in EAE and possibly MS.…”
Section: Estrogens and Multiple Sclerosissupporting
confidence: 61%
See 1 more Smart Citation
“…Morales et al [170] demonstrated that treatment with an ERa ligand is sufficient to recapitulate the estrogen-mediated protection in EAE, consistent with a report by Elloso et al [69] that demonstrated that treatment with an ERa, but not an ERb, ligand could reduce acute EAE disease severity. The degree of preservation of neuronal integrity in the gray matter of estradiol and ERa ligand-treated mice with EAE in this study was striking, and this has major implications for neurodegenerative changes that occur ''beyond the lesion" in EAE and possibly MS.…”
Section: Estrogens and Multiple Sclerosissupporting
confidence: 61%
“…The ERa selective ligand propyl pyrazole triol (PPT) provides neuroprotection and anti-inflammatory activities in brain in experimental models of neurodegenerative diseases, including ischemia [165], MPTP-induced neurotoxicity [52] and EAE ( [69,170]). The in vitro activity of PPT has been studied in neuronal cells [266], while our preliminary data demonstrate a direct anti-inflammatory activity of this ligand in microglia (unpublished results).…”
Section: Selective Er Modulatorsmentioning
confidence: 99%
“…Several earlier studies showed that estrogens (particularly E 3 ) could modulate antigen-specific immune response in autoimmune disease animal models, including those for experimental autoimmune encephalomyelitis (EAE) and collagen-induced arthritis (CIA) (Soldan et al, 2003;Palaszynski et al, 2004;Elloso et al, 2005). These autoimmune conditions are usually induced by injection of specific antigens that are emulsified with CFA.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that both ER sub-types are expressed in cells of the mouse immune system (Smithson et al, 1995;Igarashi et al, 2001;Sakazaki et al, 2002), and that both E 3 and E 2 can activate ERα and ERβ signaling in these cells to modulate immune responses via their genomic actions (Salem et al, 2000;Maret et al, 2003;Polanczyk et al, 2003;Elloso et al, 2005;Baker et al, 2004). When E 3 and E 2 exert a similar modulating effect on certain immune system functions, it is likely that their actions are mediated through activation of the ERα and/or ERβ system(s), since both estrogens can bind to and activate these two receptor systems.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects, particularly of ERa ligands on suppression of experimental autoimmune encephalomyelitis have been shown (Elloso et al 2005). E 2 has been shown to decrease neutrophil infiltration in the lung following trauma hemorrhage in mice (Hildebrand et al 2006), and a selective ERb ligand (ERB-041) was shown to have potent anti-inflammatory activity in a rat model of arthritis (Follettie et al 2006).…”
Section: Introductionmentioning
confidence: 99%